The role of change approaches in security institutional excellence - Al-Suwaidi, Sultan Abdulrahman Saif Al-Asm (Journal of Economic, Administrative and Legal Sciences, 2023)
The aim of this research is to identify the role of change approaches in security institutional excellence, identify the concept of change and change management, reveal the origin of change and its stages, analyze the persuasion approach to bring about change in the Security Institution, identify the dimensions of the participation approach to bring about change in the Security Institution and the requirements for its success, and finally analyze the: There is a statistically significant relationship between change approaches and performance excellence in the Security Institution, and the importance of the research was that change is the inevitable element in all forms and stages of administrative activity, and the process of its success is closely related to keeping abreast of the events and developments that occur about it, and subject to the effects of several internal and external factors analysis of the concept of the force approach to bring about change in the organization In order to answer the problem of the study, which was represented in whether it is possible to convince the parties that change is progress for the better, and that change from this perspective will ultimately benefit everyone, and pour into the service of work and the Security Institution The research came to a set of conclusions that there is a direct relationship between organizational change and institutional excellence in the security institution, as well as according to the force approach, all methods are used to bring about change, change is imposed on the parties concerned by force, and all forms of resistance are overcome using penalties and sanctions for anyone who violates or resists, and this approach may be effective in some emergency cases, but The researcher presented some proposals in order to implement the change and achieve the excellence of the Security Institution.security leaders should notify the concerned employees of the profits and gains that can be achieved for them as a result of the change, considering that it is an action intended to reach all individuals and the institution for the better, which contributes effectively to increasing the material and moral gains of the Security Institution's employees. the more the employees assure the management and its good management, and even the more the management.
Keywords: approaches to change; organizational excellence; approaches to power; persuasion; participation